Biocompatibility of various hydoxyapatite scaffolds evaluated by proliferation of rat's bone marrow mesenchymal stem cells: an in vitro study (Faculty of Medicine Universitas Indonesia, 2013)
Background: Scaffold (biomaterial) biocompatibility test should be performed in vitro prior to in vivo stem cell application in animal or clinical trial. These test consists of direct and indirect toxicity test (MTT assay [3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide]). Those tests were used to identify cell morphological changes, cell-substrate adhesion impairment, and reduction in cell proliferation activity. Methods: The tested scaffolds were hydroxyapatite-calcium sulphate (HA-CaSO4) (scaffold I), nano-particular HA paste (scaffold II), synthetic HA granule (scaffold III), bovine HA granule (scaffold IV), and morsellized bovine xenograft (scaffold V). Direct contact toxicity test and MTT assay [3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide] were performed on those groups. In direct contact toxicity test, we put granules of various scaffolds within plates and incubated together with mesenchymal stem cells (MSCs). In MTT assay we included phenol 20 mg/mL and 100 mg/mL group as positive control. Morphology, cell adhesion impairment, and cell growth were monitored daily until day-7. Cells counting in the direct contact toxicity test was conducted on day-7. Results: There were no changes on 24 hours observation after direct contact. On day-7, an impairment of cell adhesion to plastic substrates, changes in cell morphology, and cell death were observed, especially in scaffold I, scaffold II, and scaffold V. In MTT assay, only scaffold I, phenol 20 mg/mL, and phenol 100 mg/mL showed more than 50% inhibition at 24-hour and 7-day-observation. Extracts from scaffold II, III, IV, and V did not affect the viability and proliferation of bone marrow MSCs (inhibition value < 50%). Scaffold II, III, IV and V were proven non-cytotoxic and have good biocompatibility in vitro, no statistical significant differences were observed among the scaffold groups (p > 0.05). Conclusion: We understand which scaffold was nontoxic or the least toxic to MSCs in vitro. Scaffold IV (bovine HA granule) showed the least toxic effect to rat's bone marrow MSCs on direct contact test and MTT assay. (Med J Indones. 2013;22:202-8. doi: 10.13181/mji.v22i4.600)